The Appropriations Nature by the Real Estate Marketing in Salvador, Under the Environmental Risk Societys Context - Juliana Campos de Oliveira; Rafaela Campos de Oliveira (Revista de Direito Ambiental e Socioambientalismo, 2015)
This article aims to address the issue involving the appropriations nature by the real estate marketing, making a particular focus on the Salvador, under the presente Environmental Risk Societys context. We have been understood that real estate marketing has been earned the benefits  of  the  natural  environment  defense  considerations,  selling  a  environmental preservation  image,  but,  in  fact,  seeking  to  overvalue  their  homes  by  the  natures appropriation. For the satisfactory achievement of the intended objectives, this research will be conducted by literature sources about the urban issues and the Risk Society and the roles housing Market in the cities. In addition it will be carried out qualitative analysis of advertising material that portrays the natures appropriations practice by the real marketing estate in Salvador city, Bahia Estate, where there is a intenseve housing market activity, especially in the sense of the natural wealths appropriation in the city .